Analisis Ratio Legis Penghapusan Pasal 102 Undang-Undang Nomor 32 Tahun 2009 Tentang Perlindungan dan Pengelolaan Lingkungan Hidup - Aditya Aulia Rahman; Muh. Jufri Ahmad (Media Hukum Indonesia (MHI), 2026)
The removal of criminal sanctions for the management of Hazardous and Toxic Waste (B3) under Law Number 6 of 2023, which ratified Government Regulation in Lieu of Law Number 2 of 2022 on Job Creation into law, has generated considerable debate within the field of environmental law. Although this policy reform is intended to promote a more favorable investment climate through regulatory simplification, it also raises concerns regarding environmental protection and the effectiveness of legal enforcement against activities that may cause environmental pollution. This study aims to examine the ratio legis underlying the removal of criminal sanctions for B3 waste management following the enactment of the Job Creation Law. The research adopts a normative legal method using statutory, conceptual, and historical approaches. Primary, secondary, and tertiary legal materials were analyzed qualitatively through legal interpretation. The findings reveal that the repeal of Article 102 of Law Number 32 of 2009 reflects a shift in legal policy toward deregulation, the simplification of business licensing procedures, enhanced investment competitiveness, and the implementation of a risk-based regulatory approach. Furthermore, the policy demonstrates a transformation in the paradigm of environmental law enforcement through the application of the ultimum remedium principle, whereby criminal sanctions function as a last resort after administrative measures have proven ineffective. Nevertheless, considering the significant risks posed by B3 waste to human health and environmental sustainability, the effectiveness of this policy depends on strengthening administrative oversight mechanisms, ensuring the consistent enforcement of administrative sanctions, and enhancing the institutional capacity of government authorities to supervise and monitor environmental compliance. Therefore, the success of this legal policy relies not only on amendments to statutory provisions but also on the effective implementation of administrative supervision to ensure the continued protection of the environment.